Leaving Russia: Exit Strategies of Foreign Companies - Nikolai Duvakin; Lucky Alexis Isagalieva; Andrey Panteleev (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2023)
This study involves the compilation of a database detailing the exit of foreign companies from Russia in 2022 and the identification of their primary exit strategies. The current situation is unprecedented in its scale and has no analogues in the history of the Russian economy, therefore, it has not been sufficiently studied yet. A total of 28 industries across 25 countries were selected for the initial study. Through an analysis of exit patterns, nine primary strategies were identified, including joint venture exits, soft closings, sales to local buyers, suspension, liquidation, management buyouts, selling shares to partners, carving out to local legal entities, and sales to foreign buyers. The subsequent research stage focused on the oil and gas industry and examined the cases of its five leading companies: Shell, TotalEnergies, Equinor, Exxon-Mobil, and BP. It assessed both financial and non-financial losses incurred by these companies due to their decisions to withdraw from the Russian market. Financial losses were determined using the Discounted Cash Flow method and the Economic-Value-Added valuation method, while non-financial factors were assessed through operational indicators such as reserves and oil and gas production. The fundamental value of the above-mentioned companies was shown to comprise to $20.6 billion, $1.1 billion, $0.5 billion, $17.8 billion, and $36.5 billion, respectively. The study revealed that companies with strategically important and substantial projects in Russia, notably BP and TotalEnergies, pursued a “soft” exit strategy. Despite their decision to exit Russia, these companies continued to receive dividends and effectively retained ownership shares in assets, even though financial statements reflected impairments.